Modelo departamental e não departamental : um estudo de caso da Universidade Federal do Espírito Santo-Campus de Alegre - Oliveira, Josiléia Curty de (2018)
The departments were set up at the Brazilian federal universities (UFBs) through Law 5.540/1968 (BRAZIL, 1968). In recent years, discussions about the exclusion of academic departments from the organizational structure of universities have been portrayed as contributing to the structural and administrative innovation of these institutions. In the present work, the perception of the teachers and technicaladministrative in education about the implementation of the organizational structure without teaching departments in the academic units of the UFES - Alegre Campus was analyzed. In relation to the methodology, this research is a case study, of an applied nature, of quantitative-qualitative approach and, as far as the objectives, exploratory and descriptive. For the data collection, an opinion survey was conducted, through a structured questionnaire, with teachers and technicaladministrative personnel in education. Initially, we used the descriptive statistics of the significant variables, providing a profile of the respondents and their perception of the current organizational structure. Subsequently, the analysis was carried out using multivariate methods to identify which variables of greater statistical significance were obtained with the factorial plans and the extraction of the main components. The results of the statistical analysis were significant, since it was possible to verify that the most important factors in the perception of the servers are related to the need to change the current organizational structure. This confirms a change in the institutional culture pattern, which can bring positive perspectives for the Alegre Campus to redesign its academic and administrative units. The results also showed that there is good acceptance of the Teachers and TAEs for an organizational restructuring of the Alegre Campus with a focus on Course Colleges. At the end, an Analytical Report on the Perception of Servers on the Restructuring Process of the UFES - Campus de Alegre was carried out, which can serve as an information bank for managers and the academic community, aiming at the implementation of a new organizational structure for the Academic Units in the Campus of Alegre